Особливості вживання термінології у межах дисципліни «Українське фахове мовлення» - Ластовець, Н. О. (ХНУРЕ, 2025)
The study of professional Ukrainian language requires precise terminology usage. The course "Ukrainian Professional Language" introduces students to industry-specific vocabulary, academic writing, and professional communication standards. Effective learning strategies, such as comparative analysis, contextual application, and interdisciplinary approaches, enhance comprehension. Clear and structured explanations of terminology foster students' linguistic competence, ensuring their ability to communicate effectively in academic and professional settings.
Keywords: фахове мовлення; термінологія у межах дисципліни